FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA KEBUNTINGAN (CONCEPTION RATE) PADA SAPI POTONG SETELAH DILAKUKAN SINKRONISASI ESTRUS DI KABUPATEN PRINGSEWU - Tri Nurjanah; Madi Hartono; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
This study of the influential factors of conception rate on cattle after estrous synchronization inPringsewu Regency was held in November 2012–February 2013. This study used 278 cattlesowned by 229 breeders. This study aimed to determine the factors and factor number whichinfluenced to the conception rate after estrous synchronization in Pringsewu Regency, Province ofLampung. The method used in this study was method of census. The data analysis used in thisstudy was analysis of regression. Before doing the data analysis, coding of data of inseminatorsand breeders was done to make the analysis easier, and then being analysed on program of SPSS(Statistics Packet for Social Science). The result of this study showed that the conception rate ofbeef cattles after estrous synchronization in Pringsewu Regency was 69,42%, including in goodcategory. The factors which influenced the conception rate and associated positively were thefrequency of giving pasturage with the factor number of 3, 386, the amount of giving pasturagewith the factor number of 0,196, the shape of stable walls with the factor number of 10,371, thegiving concentrate with the factor number of 4,011, the knowledge of estrous and inseminationwith the factor number of 7,579, while associated negatively were giving water to a large numberof factors 0,181, and the knowledge of hereditary breeding with the factor number of 3,707.